Case report of gross hematuria in the nutcracker syndrome resolved by renocaval reimplantation - Banzić, Igor; Fatić, Nikola M; Pejkić, Siniša; Davidović, Lazar; Sladojević, Miloš; Končar, Igor (Vojnosanitetski pregled, 2017)
Introduction. Nutcracker syndrome is defined as a set of signs and symptoms secondary to compression of the left renal vein (LRV) in the acute anatomic angle between the aorta and its superior mesenteric branch. Case report. A 38-year-old woman with asymptomatic and “idiopathic” gross hematuria came to the Clinic for Vascular and Endovascular Surgery, Clinical Center of Serbia in Belgrade. Hematuria was documented by cystoscopy and was found to be unilateral, located to the left urethral orifice. The contrast-enhanced multidetector computed tomography (MDCT) scan showed a stenotic LRV due to the extrinsic compression in the angle formed by the ventral aorta and superior mesenteric artery (MSA), with a jet of contrast through the lumen. Considering the negative investigations for more common causes of hematuria, its incapacitating nature, and above mentioned imaging findings suggestive of the nutcracker syndrome, an indication for the open surgical correction of the LRV entrapment was established. The patient underwent reimplantation of the LRV into the more distal inferior vena cava (IVC), to relocate it out of the constrictive aortomesenteric space. Intraoperative findings were notable for blood flow turbulence in the LRV and hypertrophy of its tributaries, which were ligated. We presented the first published case in the Serbian literature on nutcracker syndrome with hematuria resolved by renocaval reimplantation. Conclusion. This case report demonstrates that renocaval reimplantation, as the open surgery technique, could be the adequate method for resolving gross hematuria in patients with nutcracker syndrome.